PENGENALAN DAN PEMANFAATAN DIGITAL DESIGN SEBAGAI PENINGKATAN SOFT SKILL WARGA DESA DANGDANG - Abdul Hafizh Ala’uddin; Agi Nurpalin; Ikhwan Naufal Yupi; Muhamad Fahmi; Muhamad Rino Setiawan; Muhammad Raihan; Muhammad Rizky Safrihza; Teguh Firmansyah; Galuh Saputri (Abdi Jurnal Publikasi, 2023)
Per the title of this community service program, the method of applying science and technology that is carried out is in the form of training and introduction to Graphic Design using Canva for the community in Dangdang Village, Cisauk District, Tangerang Regency, Banten. Skills training activities are supported by questions and answers and hands-on practice, which will be provided to the community as a tool for participating in activities using each participant's smartphone. The purpose of implementing this community service program is to improve Graphic Design skills by using the Canva application for the community. From the evaluation results and the findings we obtained during the implementation of this community service activity, this community service program has provided significant and targeted benefits for the training audience that is the target of this activity. This form of training is a very effective form of providing refreshment, additional insight, and new knowledge in graphic design in the digital entrepreneurship process.